2012
DOI: 10.1155/2012/608359
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain Trajectories in Cardiac Surgery Patients

Abstract: Poorly controlled postoperative pain is a longstanding and costly problem in medicine. The purposes of this study were to characterize the acute pain trajectories over the first four postoperative days in 83 cardiac surgery patients with a mixed effects model of linear growth to determine whether statistically significant individual differences exist in these pain trajectories, and to compare the quality of measurement by trajectory with conventional pain measurement practices. The data conformed to a linear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 58 publications
2
30
0
1
Order By: Relevance
“…The results of the two domains (pain and energy level) analyzed show the functional improvement described by the FIM on the patients form the VRG on the 1 st POD, because it is known that pain limits functional recovery [39].…”
Section: Cg Thus Showing Significant Difference On Thementioning
confidence: 91%
“…The results of the two domains (pain and energy level) analyzed show the functional improvement described by the FIM on the patients form the VRG on the 1 st POD, because it is known that pain limits functional recovery [39].…”
Section: Cg Thus Showing Significant Difference On Thementioning
confidence: 91%
“…14 Similar results were obtained in a sample of adults undergoing cardiac surgery. 16 Another study of pain trajectories of liver donor patients showed that patients who developed CPSP had higher pain intensity trajectories in the first 24 hours after surgery or an abnormal resolution of their acute pain. 10 The goals of this study were to: (1) identify and describe the various pain trajectories beginning preoperatively and for up to 12 months after surgery, (2) identify baseline predictors of trajectory group membership, and (3) identify trajectory groups that are associated with poor psychosocial outcomes 12 months after surgery in a cohort of patients undergoing TKA.…”
Section: Introductionmentioning
confidence: 99%
“…Linear growth curve modeling is appropriate for use in developing postoperative pain trajectories [10][11][12][13][14]. Repeated measures of pain yield better precision.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of pain trajectory suggests that the slope of the trajectory and not one daily score should be the target of pain control intervention [14]. There are no studies on pain trajectories specifically in trauma patients.…”
Section: Special Issue: Anesthesia and Critical Carementioning
confidence: 99%